2014
DOI: 10.4236/ojcm.2014.41002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Physical Properties of Graphene-Cement Composite for Structural Applications

Abstract: The hydration of cement generates heat due to the exothermic nature of the hydration process. Poor heat dissipation in mass concrete results in a temperature gradient between the inner core and the outer surface of the element. High temperature gradients generate tensile stresses that may exceed the tensile strength of concrete thus leading to thermal cracking. The present paper is an attempt to understand the thermal (heat sink property) and microstructural changes in the hydrated graphene-Portland cement com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 25 publications
0
50
0
4
Order By: Relevance
“…Based on the XRD and SEM tests, they speculated that the intrinsic reinforcement mechanism was that the hydration gels reacted preferentially with the functional groups on the surfaces of GONPs. In addition, the unique 2D sheet-like structure of GONPs was found to form a barrier against crack propagation so as to provide a 2D isotropic reinforcement for cement paste [14]. This is an advantage over the nanofiber-like additives, which strengthen concrete microstructure only normal to their longitudinal direction, and thus cannot arrest the microcrack growth parallel to it.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on the XRD and SEM tests, they speculated that the intrinsic reinforcement mechanism was that the hydration gels reacted preferentially with the functional groups on the surfaces of GONPs. In addition, the unique 2D sheet-like structure of GONPs was found to form a barrier against crack propagation so as to provide a 2D isotropic reinforcement for cement paste [14]. This is an advantage over the nanofiber-like additives, which strengthen concrete microstructure only normal to their longitudinal direction, and thus cannot arrest the microcrack growth parallel to it.…”
Section: Introductionmentioning
confidence: 97%
“…Graphene nanoplatelets (GNPs) and graphene oxide nanoplatelets (GONPs) are new types of nano-particles consisting of graphene stacks [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Different from pristine graphene, GONPs are oxides of GNPs, and thus contain the functional groups attained during oxidation and exfoliation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the graphenereinforced ceramic matrix composites were found to exhibit a decreased tendency to fracture, mainly because of crack bridging, crack deflection, crack tip shielding, and crack branching. Moreover, few studies have investigated the effect of graphene on the properties of cementitious materials [25][26][27][28]. Lv et al reported that the addition of 0.3% of graphene oxide in cement composites showed a remarkable increase of 78.6%, 60.7% and 38.9% in tensile strength, flexural strength and compressive strength, respectively [25,28].…”
Section: Introductionmentioning
confidence: 98%
“…Besides the proper dispersing method, preparation of new functional fillers or hybrid fillers can contribute to the development in this field of science. In the last years graphene oxide [23,24] and graphene nanoplatelet [15,25] have gathered spectacular attention as a potential material to improve self-sensing ability of cement-based materials. The entanglement of carbon nanotubes represent some major challenge for large-scale structural application.…”
Section: Sum Up; Future Directions Of Developmentmentioning
confidence: 99%